PENGARUH PEMBERIAN TABLET BESI SATU KALI SEMINGGU TERHADAP STATUS HB DAN STATUS BESI ANAK SEKOLAH PENERIMA PMT-AS - Saidin, Muhamad; Sukati, Sukati; Murdiana, Ance; Pambudi, Joko; Rustan, Effendi; Martuti, Sri; Ridwan, Endi; Muhilal, Muhilal (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
It had been conducted a study on "The Effect of Weekly Iron Supplementation on The Status of Hb and Iron among School Children Receiving PMT-AS". The main objective of the study was to investigate the effect of iron tablets supplementation to iron status of school children receiving PMT-AS. The subjects of this study was primary school children in the fourth, fifth and sicth grades in six schools receiving PMT-AS in sub-district of Sidomulyo, south Lampung. The schools were randomly assigned into three groups. The first group received iron tablets given by school teacher. The second group received iron tablets given by school teacher and under supervision of researcher (nutritionist), and the third group was control. Iron tablets containing 60 mg elemental iron were given weekly for the duration of 4.5 months. The results of study showed: 1. The percentage of anemia subjects at the begining of study in group I, II, III were 60.0%, 58.0%, and 55.1% respectively. 2. Weekly Iron Supplementatioon reduced significantly the percentage of anemia subjects (p<0.05). 3. Weekly Iron Supplementation increased Hb status and iron status significantly (p<0.05). 4. Iron tablets distribution conducted by the school teacher without supervision was as effective as iron tablets distribution under supervision of researcher. Keywords: anemia, PMT-AS (School Feeding Program), iron tablet, hemoglobin status.